2016
DOI: 10.1021/acs.jchemed.5b00612
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an In-Class Biochemistry Mini-conference on Students’ Perception of Science

Abstract: The work presented here is the summary of a 3 year study that aimed to uncover how students’ perception of science changes with the chance to participate in a mini-conference that is incorporated into the biochemistry lecture course. Students were asked to work in groups of 2 or 3 and research a topic that is related to the material covered in class. Their research was presented during the last lecture of the course, and the presentation was conducted similar to a conference poster session. The students’ grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…The undergraduate STEM curriculum in the United States consists primarily of written assessments. Regardless of the size or type of institution, oral assessments are considered a novelty. , Undergraduate students in select institutions have the opportunity to perform research, develop a thesis, and present their work as part of their graduation requirement. However, these opportunities are not widely available to all students . Work by Freeman and co-workers have shown that exam scores are a predictor of students switching out of the STEM field .…”
Section: Introductionmentioning
confidence: 99%
“…The undergraduate STEM curriculum in the United States consists primarily of written assessments. Regardless of the size or type of institution, oral assessments are considered a novelty. , Undergraduate students in select institutions have the opportunity to perform research, develop a thesis, and present their work as part of their graduation requirement. However, these opportunities are not widely available to all students . Work by Freeman and co-workers have shown that exam scores are a predictor of students switching out of the STEM field .…”
Section: Introductionmentioning
confidence: 99%
“…To the extent that cooperation is a pedagogical objective, collaborative work can be proposed, for example in poster sessions [41,42]. Poster sessions have largely been used in-class [43][44][45][46][47].…”
Section: Develop Skills Of Cooperation and Sharingmentioning
confidence: 99%
“…In addition to preparing students for the management of posters per se, poster session have been proposed to favor the work on communication skills and statistical reasoning [48]. Interestingly, the use of a poster session for evaluation, as for other alternative evaluation methods, could facilitate the inclusion of underrepresented students [41,42]. As an example we have used poster session in a biology course dealing with model organisms, each group presenting a different organism and discussions allowing to explore the pros and cons of the studied model organisms.…”
Section: Develop Skills Of Cooperation and Sharingmentioning
confidence: 99%
“…59 The implementation of a "mini-conference" approach during the biochemistry lecture that was based on student group work and peer (rather than instructor) assessment produced positive changes in non-STEM-majors' view of the nature of science. 60 Implementing games to teach metabolic pathways has been found to help student groups gain knowledge of concepts addressed during the game. 61 Using a goal-based scenario (GBS) game that dealt with a crime investigation centered on the topic of DNA has also been shown to be an effective tool to teach biochemistry concepts related to the structure/ function of DNA.…”
Section: Learner-centered Approaches To Teaching In Biochemistry Clas...mentioning
confidence: 99%
“…The implementation of a “mini-conference” approach during the biochemistry lecture that was based on student group work and peer (rather than instructor) assessment produced positive changes in non-STEM-majors’ view of the nature of science …”
Section: Different Approaches To Instructionmentioning
confidence: 99%